Mitochondrial DNA based identification of forensically important Indian flesh flies (Diptera: Sarcophagidae). (February 2015) - Sharma, Manish; Singh, Devinder; Sharma, Ajay Kumar
Highlights: 30 specimens belonging to 10 forensically important species of flesh flies were collected from north India. All the specimens were morphologically identified. A 465 bp region of mitochondrial COI gene was isolated and used for the identification. The results show the robustness of COI gene as diagnostic marker. For interspecific studies COI gene has potential to distinguish the Indian sarcophagid species. Abstract: An absolutely vital prerequisite in the forensic entomology cases is the estimation of post mortem interval (PMI). Due to similar morphological look, identification of the flesh fly fauna associated with the corpse is very difficult for nontaxonomists and needs professional hand to be dealt with. So, to simplify the identification process the application of 465 bp fragment of COI gene for differentiation of ten forensically significant species of flesh flies is demonstrated in this paper. Percentage nucleotide composition, genetic divergence and substitution rate were calculated by using the Maximum likelihood method. Phylogenetic analysis was done by Neighbour-joining tree constructed by using Tamura-3-parameter given in the MEGA5 software. The results show the robustness of COI gene as diagnostic marker, since its nucleotide variability enables dependable distinction to be drawn between species.